2021
DOI: 10.1108/ijbm-09-2021-0417
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in customer-facing financial services: a systematic literature review and agenda for future research

Abstract: PurposeThe objective of this study is to provide a systematic review of the literature on artificial intelligence (AI) in customer-facing financial services, providing an overview of explored contexts and research foci, identifying gaps in the literature and setting a comprehensive agenda for future research.Design/methodology/approachCombining database (i.e. Scopus, Web of Science, EBSCO, ScienceDirect) and manual journal search, the authors identify 90 articles published in Australian Business Deans Council … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 163 publications
3
34
0
Order By: Relevance
“…Previous research on IJBM 40,6 AI in financial services has largely examined technologies such as chatbots (Adam et al, 2021;Eren, 2021), robo-advisors (Belanche et al, 2019;Bhatia et al, 2020) and AI genetic programming (Aloud, 2017) as can be seen in Table 1. These studies provide interesting insights as to the effect of AI on consumers in service encounters, however, as suggested by Hentzen et al (2021), greater understanding is still required to examine the comprehensive effect of AI on consumers and their responses in financial service settings. Next, emotions and trust are suggested as explanatory responses (mediators) which explain how consumers react and evaluate marketing outcomes when provided financial services by AI.…”
Section: Literature Review Ai Vs Human Servicesmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research on IJBM 40,6 AI in financial services has largely examined technologies such as chatbots (Adam et al, 2021;Eren, 2021), robo-advisors (Belanche et al, 2019;Bhatia et al, 2020) and AI genetic programming (Aloud, 2017) as can be seen in Table 1. These studies provide interesting insights as to the effect of AI on consumers in service encounters, however, as suggested by Hentzen et al (2021), greater understanding is still required to examine the comprehensive effect of AI on consumers and their responses in financial service settings. Next, emotions and trust are suggested as explanatory responses (mediators) which explain how consumers react and evaluate marketing outcomes when provided financial services by AI.…”
Section: Literature Review Ai Vs Human Servicesmentioning
confidence: 99%
“…(2021) conducted a systematic review of previous research on AI in customer-facing financial services and included 90 papers in the systematic review. It was identified that there had been a significant increase in research since 2018 with 30% of articles focusing on banking and 27% focusing on financial advice and investment (Hentzen et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This special issue includes nine articles, and it is structured as follows: (1) the intersect of AI and political ideology in financial services marketing (Riedel et al , 2022; Cui, 2022), (2) financial robo-advisors (Bouhia et al , 2022; Northey et al , 2022), (3) developing AI for financial services marketing in emerging countries (Ghazwani et al , 2022; Omoge et al , 2022; Mogaji et al , 2021; Sheth et al , 2022) and (4) new theoretical and empirical approaches (Hentzen et al , 2021). Papers in each theme are subsequently discussed.…”
Section: The Selected Papersmentioning
confidence: 99%